"America Was God's Country, New York the City of Miracles". - Pridan, Ariel Yehudith (Shofar: An Interdisciplinary Journal of Jewish Studies, 2026)
This article offers a close reading of Job: The Story of a Simple Man (1930) by Joseph Roth, delving into the novel's intricate engagement with political and spatial concerns intertwined with the diverse possibilities for "modern redemption" confronted by Jews in the early twentieth century. Through the narrative of the Singer family's migration from an Eastern European shtetl to New York City, Roth critiques the process of urban modernization and dismisses the spatial transformation into the Western metropolis as a viable answer to the "Jewish question" (Die Judenfrage). Employing biblical allusions, Roth redirects the potential for modern "Promethean redemption" toward theological and eschatological dimensions. In doing so, Roth also contributes to the perpetuation of the Habsburg Myth by exploring the political potential to transcend the constraints of segregation and binarism inherent in the modern nation-state.